Eco-friendly Plant-based Disease Control: Exploring Terminalia Species Extracts as Biopesticides against Fungal Pathogens (Indian Journal of Biochemistry and Biophysics (IJBB), 2025)
The increasing reliance on synthetic fungicide to combat fungal diseases in vegetable crops has highlighted concerns about pathogen resistance, human health risks, and environmental safety. As a result, research into plant-based bio-pesticides has generated much interest as a viable alternative. This study focuses on the antifungal efficacy of Terminalia alata, Terminalia bellirica, Terminalia arjuna, and Terminalia catappa against fungal pathogens affecting economically important vegetable crops-brinjal (Solanum melongena), tomato (Solanum lycopersicum), cauliflower (Brassica oleracea), spinach (Spinacia oleracea), and lady finger (Abelmoschus esculentus). Ten fungal pathogens (Phomopsis vexans, Aspergillus niger, Colletotrichum fructicola, Alternaria solani, Peronospora parasitica, Cladosporium spp., Sclerotinia sclerotiorum, Stemphylium botryosum f. sp. spinaciae, and Rhizoctonia solani, Fusarium oxysporum,) were isolated and identified using morphological, cultural, and 18s rRNA gene analysis. The antifungal activity of six solvent extracts like, chloroform, ethanol, petroleum ether, hexane and water of leaves, bark and fruits of four Terminalia sp. were investigated. Ethanolic extracts demonstrated the highest antifungal efficacy, with Terminalia bellirica and Terminalia arjuna fruit extracts exhibiting remarkable inhibition percentages (≥90%) against Colletotrichum fructicola and Peronospora parasitica. Although water and hexane extracts showed somewhat less inhibitory effects, chloroform and petroleum ether extracts also exhibited significant antifungal properties. In terms of mycelial growth inhibition and percentage inhibition, ethanolic extracts consistently outperformed other solvents. Phytochemical analysis revealed the presence of biologically active compounds such as flavonoids, alkaloids, tannins, phenols, saponins, terpenoids, glycosides and sterols, which may be responsible for the strong antifungal effects of the study. The findings suggest that potential of Terminalia species as a viable source of natural biological pesticides, that can act as a efficient, sustainable and environmentally beneficial, alternative to chemical fungicides. Further studies are advised to isolate, purify and characterize the active antifungal components and evaluate their field application in different agro-climatic regions. In order to improve crop protection, lessen the impact on the environment, and promote sustainable agricultural practices, the study emphasizes the necessity of implementing plant-based disease management measures.